НОВЕЙШИЕ ИССЛЕДОВАНИЯ ПАЛЕОКЛИМАТА УРАЛА ЗА ПОСЛЕДНЕЕ ТЫСЯЧЕЛЕТИЕ ПО ГЕОТЕРМИЧЕСКИМ ДАННЫМ - Литовский (Litovskiy Vladimir), Владимир Васильевич (Географический вестник=Geographical bulletin, 2017)
Приводятся сведения об исследованиях палеоклимата на Урале за последнее тысячелетие по геотермическим данным. Приведены основные результаты таких исследований NEW RESEARCHE OF THE URALS PALEOCLIMATE FOR LAST MILLENIUM DEDUCATED FROM GEOTERMAL MEASUREMENTS Data on paleoclimate research on the Urals for the last millennium deduced from geothermal measurements are submitted. The basic results of such research are analyzed in a historical scientific context.